Symptoms of herpesvirus infection in reproductive disorders in married couples - E. K. Shushakova; V. S. Markina; S. V. Nikolaeva; T. A. Ruzhencova (Лечащий Врач, 2022)
The aim of the study was to determine the clinical and laboratory features of the course of herpetic infection in married couples with impaired reproductive function. Patients and methods. The study by continuous screening included 149 married couples who complained of reproductive dysfunction. The main group included 80 married couples who had signs of urogenital herpetic infection, and the comparison group consisted of 69 married couples who did not have markers of HSV-1, 2 infection. Clinical, laboratory and ultrasound deviations were evaluated in the compared groups. It was revealed that 58.75% of patients from the main group and 38.75% in the comparison group had various complaints when assessing the symptoms among women. 43.75% of patients complained among men of the main group, and in the comparison group – 6.25%. Gynecological examination of women with HSV-1, 2 more often revealed cracks in the posterior adhesions, vesicular erosive elements of the external genitalia, contact bleeding, enlargement of the uterus and enlargement of inguinal lymph nodes. Laboratory examination of the spermogram in the vast majority of patients of the main group revealed teratozoospermia. Detection of HSV-1, 2 by the culture method in 100% of cases, along with the detection of antibodies of class IgA or IgM (less often) confirms infection. It was concluded that it is necessary to take into account the probability of damage to the urogenital tract of HSV-1, 2 when examining couples with reproductive disorders in the form of infertility or undeveloped pregnancy. Complaints, anamnesis and examination data should be taken into account to confirm or exclude significant infection with herpes simplex virus. The most informative are the culture method, as well as serological with the detection of IgA class antibodies among the laboratory methods for assessing the significance of infection associated with HSV-1, 2. Couples should be prescribed antiherpetic therapy if infection is confirmed.